Assessment Of Serum ALT Levels In Chronic Hepatitis C Patients In Accordance With Gender - Zuhair Ali Rizvi, Malik Shehryar, Muhammad Umer, Muhammad Asad, Salman Majeed, Hamza Waqar Bhatti, Muhammad Ali Hafeez, Zuhair Ali Rizvi, Malik Shehryar, Muhammad Umer, Muhammad Asad, Salman Majeed, Hamza Waqar Bhatti, Muhammad Ali Hafeez (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Introduction: Hepatitis C virus is an RNA virus that is affecting almost 170 million people worldwide. Hepatitis C is also associated with increased incidence of chronic liver diseases, liver cirrhosis and hepatocellular carcinoma. Therefore serum levels of ALT are considered to be the more specific indicator of hepatocellular damage than serum levels of AST. Serum ALT levels vary according to age and gender. Materials And Methods:This is a descriptive cross sectional study that was conducted from September 2016 to April 2017 at Centre of Liver Diseases of Holy Family Hospital, Rawalpindi after approval from Institutional Research Forum of Rawalpindi Medical University. Consecutive nonprobability sampling technique was used. The findings of serum ALT levels were classified into 5 groups: <40u/l, 41-60u/l, 61-80u/l,81-100u/l and >100u/l. Normal value of serum ALT levels was <40u/l. Patients were divided into 5 age groups: 10-25 years, 25-40 years, 40-55 years, 55-70 years and >70 years. The data was analyzed using SPSS v22. Frequency and Percentages were calculated for gender, age and serum ALT levels. Results:405 (198 male and 207 female) patients were included in this research. Mean ALT levels in male patients were 89.5u/l while in female patients were 70.4u/l. The difference between their mean values was significant (P=0.016). Serum ALT levels of 24.2% (98) patients were within normal range (<40u/l) while they were deranged (>40u/l) in 75.8% (307) patients. Serum ALT levels were higher in female patients in all age groups Conclusion: It was concluded that serum ALT levels vary significantly with age and gender. Elevation of serum ALT is seen more frequently in male than in female patients although mean ALT levels are higher in female patients in all age groups than in male patients.